Target-shape dependence in a simple model of receptor-mediated endocytosis and phagocytosis - Richards,D; Endres,RG (Proceedings of the National Academy of Sciences of the United States of America, 2016)
Along with other forms of internalisation, phagocytosis and receptormediatedendocytosis are vitally important for many cell types, rangingfrom single-cell organisms to immune cells. It is known experimentallythat engulfment in both cases depends critically on particleshape and orientation. However, most previous theoretical workhas focused only on spherical particles and hence disregards the widerangingparticle shapes occurring in nature, such as those of bacteria.Here, by implementing a simple model in one- and two-dimensions, wecompare and contrast receptor-mediated endocytosis and phagocytosisfor a range of biologically-relevant shapes, including spheres, ellipsoids,capped-cylinders and hourglasses. We find a whole range of different engulfmentbehaviours with some ellipsoids engulfing quicker than spheres,and that phagocytosis is able to engulf a greater range of target shapesthan other types of endocytosis. Further, the two-dimensional modelcan explain why some non-spherical particles engulf quickest (not at all)when presented to the membrane tip-first (lying flat). Our work revealshow some bacteria may avoid being internalised simply by their shape,and suggests shapes for optimal drug delivery.